Synthesis, Characterization, and Bioactivity Studies of the Schiff Base Ligand and its Zinc(II) Complex - Muhammad Salih, Nabaz A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
One of the largest concerns to global health in recent decades has been identified as the growth of bacteria resistance to antibiotics. The Schiff base (SBs) and the zinc(II) SBs complex compounds category have attracted a lot of interest because of their function in chemical syntheses and their potential for bioactive and pharmacological effects. The present study includes the synthesis of various SBs with different substituents. Equimolar mixtures of benzaldehyde derivatives (1, 2) and aniline derivatives (3, 4) are used to carry out a series of condensation reactions to get compounds (5-7). By stoichiometrically combining Zn (II) acetate and ZnCl2 separately with the SBs ligand (7) in ethanol, it has been possible to prepare the SBs zinc(II) complex (8). The structure of the ligand and its metal complex are analyzed using (Fourier transform infrared spectroscopy, 1H-NMR, 13C-NMR) spectroscopy, scanning electron microscopy, and liquid chromatography–mass spectrometry. Moreover, the synthesized compounds are verified in vitro against Escherichia coli Gram negative, Staphylococcus aureus Gram positive, and fungi (Candida albicans). Compounds (5, 7, and 8) indicated significant growth inhibition against E. coli Gram negative and fungi (C. albicans) with different inhibition zones starting from 7 to 17.5 mm.